Erobringen af Grønland: Opdagelsesrejser, etnologi og forstanderskab i attenhundredetallet - Rud, Søren (Historisk Tidsskrift, 2013)
The Conquest of Greenland: Expeditions, Anthropology and Colonial Management in the 19th CenturySealing - and the artefacts associated with it - was the most essential feature of native authenticity in the Danish colonizers’ perception of the Greenlanders in the later half of the 19th Century. This specific interpretation of Greenlandic culture manifested itself in the colonial administration by way of a peculiar institution, the so-called ‘Local Board Arrangement’ (in Danish: “forstanderskabsordningen”) from 1857 (permanent from 1862-63). Here, a corporate body of colonial officials and local sealers, recognized for their proficiency in the trade, would distribute aid to those community members who were in need. A sealer who served as council member earned a share of an eventual surplus. The expected outcome, an economical administration of the funds, translated into an incentive for others to engage in useful work, rather than rely on a meagre public assistance. Privileges and benefits for sealers thus became institutionalised, providing an ideological protection of the traditional culture of sealing. In recent studies of 19th Century colonialism in Greenland this development has been interpreted as a result of the colonizers’ economic strategy, aiming at making the Greenlanders remain sealers in order to secure a steady supply of fur and blubber. The present study shows that the way the Greenlanders were perceived in the 19th Century is connected with the distinctly modern way of representing “the other” in the language of comparative anthropology. Different native people were thus represented through a typology generated by scholarly activity, associating each one of them with characteristic features. Expeditions to the as yet uncolonized east coast of Greenland were crucial to the emergence of the most common general understanding of Greenlandic culture in the 19th Century. The picture of the kayak paddling sealer, established through anthropological surveys, became the celebrated standard by which the colonized Greenlanders were measured.